António Francisco Cardim, la misión del Japón y la representación del martirio en el mundo portugués altomoderno - Palomo, Federico (2015)
This paper explores the contribution of Portuguese Jesuit António Francisco Cardim’s work entitled Elogios, e ramalhete de flores borrifadocom o sangue dos religiosos da Companhia de Iesu (Roma 1646/Lisboa 1650) to laying the textual and visual foundation for the Society of Jesus’ discourse on, and representations of, martyrdom in the 16th and 17th centuries. The paper discusses first the circumstances of the preparation and circulation (in manuscript and print) of the volume for propaganda and spiritual education purposes. Additionally, in the light of the contemporaneous production on Japan, the paper explores the images used in the printed editions of the Elogios, especially their roots, their relation to the narrations, and the way in which images and text reflected a perception of martyrdom well ingrained in the Jesuit discourse.